Parent Quality of Life and Developmental Outcomes of Young Children - Toh, Evelyn Kheng Lin (Curtin University, 2024)
Parents of young children face challenges that affect their Quality of Life (QoL). This thesis examines how parent QoL relates to early child development and how it is assessed. One study analysed QoL in parents of two-year-olds; another reviewed QoL assessment tools for parents of children under five. A positive relationship was found between parent QoL and child social-emotional development. Findings suggest a need for a universal framework to assess parent QoL to inform intervention strategies.